FRI0214 Disease Activity and Risk of Cardiovascular Disease in Patients with Ankylosing Spondylitis with High and Low Body Mass Index. (9th June 2015) - Berg, I.J.; Semb, A.G.; van der Heijde, D.; Kvien, T.K.; Dagfinrud, H.; Hisdal, J.; Provan, S.A.
Abstract : Background: Patients with ankylosing spondylitis (AS) have increased risk of cardiovascular disease (CVD), but the mediators of this increased risk are not known. Obesity is related to increased risk of CVD in the general population. Adipose tissue is an endocrine organ secreting pro-inflammatory cytokines which may be relevant both to the pathology of inflammatory diseases and CVD. Objectives: To explore the impact of body mass index (BMI) on disease activity and CVD risk in AS. Methods: Cross-sectional study of 159 AS patients diagnosed according to the mNY criteria. Data-collection included questionnaires, blood samples and clinical examination. Carotid intima-media thickness (c-IMT) was measured by ultrasound. Height (m) and weight (kg) were measured and BMI was calculated (kg/m 2 ).The patients were categorized according to the BMI, with cut-off value between normal weight and over weight: BMI<25 kg/m 2 (BMI-low) and BMI≥25kg/m 2 (BMI-high). We compared markers of disease activity and CVD risk factors between the BMI-low and BMI-high group in linear regression models with adjustments for age, gender and smoking habits. Additional adjustments for use of non-steroidal anti-inflammatory drugs (NSAIDs) were also performed. Results: The AS patients had comparable age (years) in both groups (BMI-low vs. BMI-high), mean (SD) 50.5 years (13.2) vs. 50.5 years (11.3), respectively, but the BMI-low differed from the BMI-high regarding: male gender, 53% vs. 71%, p=0.02; CRP (mg/L), median (IQR) 2 (1-5) vs. 5 (2-13) p=0.003; use of NSAIDs, 56% vs. 74%, p=0.01. In regression analyses the BMI-high group had higher ASDAS and BASDAI than the BMI-low group. High BMI was associated with lower high-density lipoprotein (HDL), higher triglycerides, total cholesterol/HDL ratio, systolic and diastolic blood pressure as well as c-IMT (table ). Additional adjustment for use of NSAIDs did not alter results. Conclusions: AS patients with high BMI had worse disease activity, increased traditional CVD risk factors and increased c-IMT. Thus, obesity can be a common factor related to both disease activity and increased CVD risk and should be addressed in future observational studies in AS and considered as a potential confounding variable in future randomized controlled clinical trials. Disclosure of Interest: None declared